2007
DOI: 10.1063/1.2787967
|View full text |Cite
|
Sign up to set email alerts
|

The electronic structure change with Gd doping of HfO2 on silicon

Abstract: Gd-doped HfO2 films deposited on silicon substrates undergo a crystallographic change from monoclinic to fluorite (cubic) phase with increasing Gd concentrations. The crystallographic phase change is accompanied by a small increase in the valence bandwidth and in the apparent band offset in the surface region. Electrical measurements show pronounced rectification properties for lightly doped Gd:HfO2 films on p-Si and for heavily-doped Gd:HfO2 films on n-Si, suggesting a crossover from n-type to p-type behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 26 publications
6
34
0
Order By: Relevance
“…Of course f shell delocalization in metallic systems can also occur, but is more expected for the 5f levels, and Joyce and Durakiewicz, and their colleagues [5][6][7][8][9] and others [10] also found clear evidence of dispersion in the uranium 5f levels in uranium and uranium compounds. In the Gd 3+ and mixed valence systems, Gd 4f hybridization with nearest neighbor atoms is expected [11,12] and observed. In ErAs(100), strong 4f hybridization is implicated, and a direct confirmation of an occupied 4f band structure might be inferred from the data but could not established [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course f shell delocalization in metallic systems can also occur, but is more expected for the 5f levels, and Joyce and Durakiewicz, and their colleagues [5][6][7][8][9] and others [10] also found clear evidence of dispersion in the uranium 5f levels in uranium and uranium compounds. In the Gd 3+ and mixed valence systems, Gd 4f hybridization with nearest neighbor atoms is expected [11,12] and observed. In ErAs(100), strong 4f hybridization is implicated, and a direct confirmation of an occupied 4f band structure might be inferred from the data but could not established [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…We have compared the occupied density of states for Gd-doped HfO 2 for various levels of Gd doping, observing changes that could be attributed to either increasing Gd concentration or the monoclinic to cubic structural phase change that also accompanies increased doping levels [12]. To better assess the Gd 4f interaction with the oxygen nearest neighbors, it is essential to compare the n-type Gd-doped HfO 2 with n-type Gd 2 O 3 , as both are in the monoclinic phase when grown on Si(100) by pulsed laser deposition.…”
Section: Introductionmentioning
confidence: 99%
“…This Gd doping concentration is consistent with the experimental observations. 4,6 The Gd doping concentration we predict at which the phase transition occurs is close to the value of 13% estimated based on the structural energy difference at the Gd concentration of 3.125% (i.e., one doping Gd atom in the 96-atom supercell). 8 The authors 8 also predicted that the cubic phase is more stable than the tetragonal phase when the Gd doping concentration greater than 6.7%.…”
mentioning
confidence: 99%
“…4 The RE doping also enlarges the band gap, increases the permittivity, and suppresses the formation of oxygen vacancies. 12 Recent experimental studies 4,6 found when the Gd doping is beyond a certain concentration around 15%-20% the doped HfO 2 is completely transformed to the tetragonal phase. The density functional theory (DFT) calculations were also used to investigate the phase stability, point defects and defect complexes in Gd-doped HfO 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation